Decrease of microglia and fatty liver in obese mice by germinated Sang-Yod rice - Nuntika Wangpradit; Supattra Prom-in; Jaya Kumar; Kien Hui Chua; Jasadee Kaewsrichan (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2020)
Our previous study indicated that learning and cognition of obese mice were enhanced by germinated Sang-Yod rice intervention. We recently discover that inferior effects of high fat diet on lipid metabolisms and functions of two vital organs, including the liver and the brain are attenuated by germinated Sang-Yod rice. Thirty-two male C57BL/6J mice are divided into 4 groups (n = 8), and distinctly assigned to receive a different diet for 12 weeks, including normal diet (CONTROL group), high fat diet (HFD group), high fat diet plus 20 mg simvastatin/kg/day (POSITIVE group), and high fat diet plus 0.5% germinated Sang-Yod rice/kg/day (HFD-GR group). Biochemical and histological assessments are performed using blood and tissue samples, respectively. The levels of blood glucose, triglycerides, and high-density lipoproteins for all groups of mice are not different. Increases of low-density lipoprotein and total cholesterol concentrations and the albumin/globulin ratio are found for mice fed with high fat diet. The activities of alanine transaminase and aspartate transaminase enzymes are not different among these groups of mice. Fat degeneration, cytoplasmic vacuoles, and lipid droplets in the livers of mice treated with simvastatin and germinated Sang-Yod rice are reduced. Lastly, cells of the prefrontal cortex of these treated mice are morphologically normal with an absence of microglia. In contrast, microglia is simply observed in this brain area of mice in HFD group. Limitation of high fat in foods should be attended to maintain healthy life.